The Ninth Symphony of Beethoven, Its Rich History - Shiflett, Campbell (Current Musicology, 2021)
Adrienne Rich’s poem “The Ninth Symphony of Beethoven Understood at Last as a Sexual Message” has become a fixture in musicological accounts of Beethoven and the Ninth ever since its introduction to the discipline in an influential essay by Susan McClary. But though Rich’s work has been cited in numerous books and articles in the intervening decades, it has remained yoked to McClary’s text, with critics rarely considering the poem on its own terms. This paper considers what is at stake in our discipline’s reliance on Rich’s “Beethoven” poem. After taking stock of its use at the hands of musicologists since the publication of Feminine Endings, asking to what end authors reference Rich’s work, it returns to the poem in order to stage a more explicit confrontation with its text, reestablish its connections to contemporary discussions of Beethoven and feminism, and consider its significance to musicology.